Mewujudkan Good Governance Melalui Penguatan Budaya Birokrasi - Jayadi Jayadi; Maria Magdalena Widiantari; Zulin Nurchayati; Endang Murti (Jurnal Ilmu Sosial dan Ilmu Politik)
Organizational culture in the bureaucratic environment is often one of the problems that hinder the realization of good governance. On the other hand, the organizational culture that develops cannot be separated from the paternalistic Javanese culture. This makes the character of bureaucratic apparatus behavior more textually patterned based on applicable formal provisions. As a result, government officials cannot make decisions when facing obstacles in carrying out their duties, especially those related to public services. This condition can be overcome by providing flexibility for bureaucratic apparatus to be more creative in taking effective and success-oriented actions in carrying out their duties. This research shows the influence of bureaucratic strengthening efforts on the realization of good governance by eliminating unproductive Javanese cultural values so as to improve the quality of public services. The results reveal that an empowered bureaucracy with flexibility and results orientation is able to respond to community needs more quickly and precisely. In addition, the elimination of unproductive values in Javanese culture is proven to encourage innovation and initiative among bureaucratic apparatus, which ultimately improves the efficiency and effectiveness of public services.